2014
DOI: 10.1021/nn503960h
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Biomedical Applications of Amyloid Oligomer Nanoparticles

Abstract: Amyloid oligomers are nonfibrillar polypeptide aggregates linked to diseases, such as Alzheimer's and Parkinson's. Here we show that these aggregates possess a compact, quasi-crystalline architecture that presents significant nanoscale regularity. The amyloid oligomers are dynamic assemblies and are able to release their individual subunits. The small oligomeric size and spheroid shape confer diffusible characteristics, electrophoretic mobility, and the ability to enter hydrated gel matrices or cells. We final… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 71 publications
1
28
0
Order By: Relevance
“…1À3 The structure of the species 4 and the nature of its interaction with membranes have therefore attracted intense scrutiny. 5 In the case of Alzheimer's amyloid-β, some solution-state structural parameters of the early oligomeric species 6,7 have been obtained recently.…”
mentioning
confidence: 99%
“…1À3 The structure of the species 4 and the nature of its interaction with membranes have therefore attracted intense scrutiny. 5 In the case of Alzheimer's amyloid-β, some solution-state structural parameters of the early oligomeric species 6,7 have been obtained recently.…”
mentioning
confidence: 99%
“…Self‐assembled amyloid fibril networks or microgels from peptides have previously been suggested as potential drug‐delivery systems . The reported RFFFR spheres and fibers may also be used for such applications.…”
Section: Resultsmentioning
confidence: 99%
“…As oligomer binding to cellular structures of low polarity, and specifically lipid assemblies, may be a key step within the pathophysiology of Aβ peptide [41,42], addressing this question could be of significant biological impact. The reversibility of this β-to-α switch could be of practical relevance for understanding and devising peptide disaggregation/ re-aggregation protocols to be applied during loading or coupling of low-molecular-weight compounds to oligomeric Aβ assemblies in the course of derivatisation for diagnostic or therapeutic purposes [6]. As we have shown here, such nanoscale assemblies should adopt their initial principal architecture [5,6] upon exposing them to a physiologically compatible aqueous environment.…”
mentioning
confidence: 88%
“…Nevertheless, our recent studies have shown that these aggregates possess a compact, quasi-crystalline architecture with significant nanoscale regularity and that they bear potential as carriers for fluorescent dyes or iron oxide nanoparticles for medical applications [6].…”
mentioning
confidence: 99%